Methods of Calculating Function Range Calculations in Accuracy Assessment. Evaluation of Parametric Determination of Equation - B.M .Akhmedov (Zien Journals, 2023)
In this article, the evaluation method of determining the equalization of the function wave by the parametric method is considered. In this case, calculation of the weight of the function in the parametric method of equalization, calculation of the weight coefficients according to the Ganzen method, . t Calculation of weights of unknowns, Weights of last two unknowns, Calculation of function weights, Calculation of function weights in complementary graph, Complementary graph j t Issues focused on the requirements for calculating the weight of the unknown and assessing accuracy are covered. Also, an example of accuracy assessment is given as an example
Keywords: reference; geodetic coordinates; triangulation network